find

Asked by  | 3rd May, 2008, 06:48: PM

Expert Answer:

   P ( x ) = x3+ 3 x2 + 3 x + 1 divided by g( x) =5 + 2x then

 p ( - 5 / 2 ) =  ( - 5 / 2)3 + 3 ( - 5/ 2 )2 +3 ( -5/2) + 1

                   =  -125 / 8 + 3 ( 25 / 4) - 15 / 2 + 1

                  = -125 / 8 + 75 4 - 15 / 2 + 1 = - 27 / 8 is the remainder by remainder theorem.

 P ( a ) =  a3 + 3 a2+ 3 a + 1

Answered by  | 4th May, 2008, 05:21: PM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.